TWO NEW SPECIES OF BOLEODORUS (NEMATODA: TYLENCHIDA) FROM MANIPUR, INDIA - L. BINA; N. MOHILAL; M. PRAMODINI; M. MANJUR SHAH (The Bioscan, 2012)
Two new species of Boleodorus, B. longicaudatus sp. nov. and B. spinocaudatus sp. nov. were found associated with mulberry plants in Manipur, India and were described. Boleodorus longicaudatus sp. nov. is characterised by body length = 0.43-0.72 mm, a = 25.4-28.3, b = 7.05-9.2, c = 4.88-6.24, c´ = 8.66-12.4, V = 64.9%-74.4%, G1= 64.9-74.4, oesophagous = 61.2-72.4 μm, spear = 8.5 μm, and tail = 88.5-92.2 μm. Boleodorus spinocaudatus sp. nov. is characterised by body length = 0.60-0.69 mm, a = 25.5-36, b = 6.6-10.7, c = 7.5-13, c´= 4.6-6.7, V = 75.9%-82.6 %, G1= 48.7 – 81.3, oesophagous = 64.6-96.9 μm, spear = 8.5-10.2 μm, and tail = 49.379.9 μm.